Language view of the world in the paradigm of scientific and technical translation - Широков, Володимир Анатолійович; Купріянов, Євген Валерійович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”)
The present article is devoted to essential problems of elaborating the phenomenological theory of special-purpose language in the paradigm of scientific and technical translation. The phenomenological nature of special-purpose language has been established, the components of its system (language triad “structure – substance – subject”) as well as their role in scientific and technical translation have been determined. In the context of the phenomenological approach, the theoretical grounds for phenomenological theory of special-purpose language as a tool for scientific and technical translation have been elaborated.